2021
DOI: 10.1039/d1ra00049g
|View full text |Cite
|
Sign up to set email alerts
|

Polysorbate-80 surface modified nano-stearylamine BQCA conjugate for the management of Alzheimer's disease

Abstract: Acetylcholinesterase (AChE) inhibitors such as donepezil, galantamine and rivastigmine are used for the management of dementia in Alzheimer's Disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Animal model results showed that drug uptake in the brain increased four-fold for PBCA NPs coated with 1% PS 80 compared to free drugs. Several studies have demonstrated that PS 80-coated NPs can improve drug accumulation in the brain [124][125][126][127][128][129][130][131]. It has been reported that brain targeting of PS 80-coated NPs is closely associated with the interaction between PS 80 coating and brain microvessel endothelial cells [132].…”
Section: Ps-coated Nps For Efficient Bbb Transportmentioning
confidence: 99%
“…Animal model results showed that drug uptake in the brain increased four-fold for PBCA NPs coated with 1% PS 80 compared to free drugs. Several studies have demonstrated that PS 80-coated NPs can improve drug accumulation in the brain [124][125][126][127][128][129][130][131]. It has been reported that brain targeting of PS 80-coated NPs is closely associated with the interaction between PS 80 coating and brain microvessel endothelial cells [132].…”
Section: Ps-coated Nps For Efficient Bbb Transportmentioning
confidence: 99%
“…Current applications of surfactants in the manufacture of NP for biomedical applications seek a vectorization phenomenon to facilitate drug release at receptor sites [12]. In this regard, the participation of surfactants represents a multifunctional ingredient that usually requires adsorption by covalent crosslinking to guarantee better performance in biological pathways [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They found that PS 80-NPs exhibited the highest neural cellular uptake and BBB permeability . Additionally, PS 80 has other advantages such as low cost, good stability, and minimal immunogenicity and has been approved to be used in some pharmaceutical and food industries. However, to our knowledge, PS 80-coated NPs have never been used to transfer AMF to the brain for RIBI prophylaxis. Our initial screening studies demonstrated that DAPP NPs exhibited good neural cellular uptake.…”
Section: Discussionmentioning
confidence: 99%